Cross-Border Dynamics of IP Modularity: International Patenting in LEDs and Lithium-Ion Secondary Battery Technology - Peter M. Bican; Dirk Caspary; Carsten C. Guderian (Management International Review, 2022)
To profit from their inventions, multinational enterprises rely on various appropriation and internationalization strategies. Intellectual property modularity serves as a reliable option to master the tradeoff between owning the "right" (i.e., valuable) patents in a technology and sharing other "less valuable" patents to spur innovation and foster technology dissemination. Through an inductive, multi-case approach looking at light-emitting diodes and lithium-ion secondary battery technology, we expand prior intellectual property modularity to incorporate internationalization effects across borders. Relying on patent classifications, we trace the development of these two technologies and key multinational enterprises in various countries longitudinally from 1990 to 2018. We introduce the Dynamic IP Modularity Application Matrix and demonstrate that integrating the firm and country levels yields insights into dynamic internationalization developments, particularly when considering the drawbacks to intellectual property modularity. Herein, decision-makers need to secure not only currently valuable but also potentially valuable intellectual property to successfully apply an international intellectual property modularity value capture strategy.
Keywords: 330; Cross-border development; Intellectual property modularity; Internationalization; Multinational entities; Patents; Technology dissemination